2018
DOI: 10.1177/1054773818758171
|View full text |Cite
|
Sign up to set email alerts
|

Dark and Bright—Two Sides of Family-Centered Care in the NICU: A Qualitative Study

Abstract: Nurses in the Neonatal Intensive Care Unit (NICU) have an important role in implementing family-centered care (FCC). The aim of the study was to explore the lived experiences of NICU nurses on implementing FCC. An interpretative phenomenological study was conducted and 11 employed nurses were interviewed from April 2015 to February 2016. The data were analyzed through the Diekelmann, Allen, and Tanner approach. Four main themes of "strain to achieve stability," "bewildered by taking multiple roles," "accepting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 17 publications
0
20
0
2
Order By: Relevance
“…Also, social workers' presence at the unit is necessary, because they are responsible for providing support for the family. Therefore; the lack of psychologists and social workers has contributed to nurses' occupational burnout (Benzies, Shah, Aziz, Lodha, & Misfeldt, 2019;Mirlashari, Valizadeh, Navab, Craig, & Ghorbani, 2018).…”
Section: Fcc Implementation and Contextmentioning
confidence: 99%
“…Also, social workers' presence at the unit is necessary, because they are responsible for providing support for the family. Therefore; the lack of psychologists and social workers has contributed to nurses' occupational burnout (Benzies, Shah, Aziz, Lodha, & Misfeldt, 2019;Mirlashari, Valizadeh, Navab, Craig, & Ghorbani, 2018).…”
Section: Fcc Implementation and Contextmentioning
confidence: 99%
“…A study reported that mothers experienced more stress than fathers in areas related to the ward's sounds and lights, staff behavior and communication, NICU-related parental role, and the infant's health and behavior. The most stressful factor for parents was the change in their role after their infant›s admission to NICU [23]. Another study showed that parents of premature newborns had higher levels of stress and anxiety even two months after discharge of their infants from the hospital compared to the parents of full-term infants [24].…”
Section: Discussionmentioning
confidence: 99%
“…29 International study that explored the experiences lived by nurses in the PFCC implementation in assistance practices in the Neonatal ITU, showed that despite they wish that all the members of the family, such as brothers or grandparents visit the child, they were obliged -due to the internal policies of the unit to prevent the entry of these members of the family due to the questions related to disturbances, management and infection control. 30 Family inclusion in policies and practices Botelho LRM, Anísio NF, Cruz AC, Santos NC, Angelo M…”
Section: Discussionmentioning
confidence: 99%
“…10 The nursing team a play fundamental role in the PCCC planning, implementation and evaluation, however, although is close to the patients and their families in their daily activities, it should assume alone and exclusively the responsibility for the PFCC implementation, as patients, family members and all the multiprofessional team should be included in all the stages, what includes the planning, the development and the evaluation of policies and guidelines related to this care approach. 30…”
Section: Discussionmentioning
confidence: 99%